Prevalence of hyperprolific authors in sports medicine and musculoskeletal health and implications on research attention - Serena Uppal; Haneef Khan; Michelle Helen Cruickshank; Michelle Ghert (PLoS ONE, 2026)
Purpose The phenomenon of hyperprolific authorship has raised concerns about research quality, academic integrity, and the sustainability of publication practices across scientific disciplines. Hyperprolific authors (HA) are defined as those publishing 72 or more papers annually, while almost hyperprolific authors (AHA) publish 61–72. This study aimed to identify and characterize extremely productive (EP) authors, defined as HA and AHA, in sports medicine and musculoskeletal health research and assess their scientific impact. Methods We analyzed publications from the top 20 CiteScore-ranked journals in sports medicine and musculoskeletal health between 2020 and 2024 using the Scopus database. Authors were classified as HA or AHA based on annual publication volume. Metadata was extracted regarding publication counts, authorship positions, institutional affiliations, and geographic distribution. Citation impact and scholarly attention were evaluated using h-index and total citation counts. Results Among 16,983 articles and 68,209 unique authors, 222 (0.45%) were classified as EP authors (125 HA, 97 AHA). Five authors maintained HA status across all five years, with the most prolific author publishing 1,174 papers and a peak annual output of 262. EP authors were concentrated in Europe (42.3%), Asia (28.4%), and the Americas (22.5%), especially in Germany, Japan, China, and the United States. Most EP authors were middle authors (median 59.8%–60.9%), with low first authorship (1.9%–2.1%) and higher last authorship rates (22.6%–27.0%). Despite concerns about volume, EP authors demonstrated substantial research attention, over their entire career, as measured by citation metrics: mean h-index 79.9 and mean total citations 35,654. Conclusions Extremely productive authors comprise a small but influential subset of researchers. Their high output is not necessarily at the expense of research attention, but the concentration of productivity among a limited group raises important questions about authorship norms, research equity, and global representation.